Spontaneous color preferences in rhesus monkeys: What is the advantage of primate trichromacy? - Skalníková, Petra; Frynta, Daniel; Abramjan, Andran; Rokyta, Richard; Nekovářová, Tereza (Behavioural processes, 2020)
Color perception and color signaling play an important role in various aspects of animal behavior. However, in mammals, trichromatic vision characterized by three retinal photopigments tuned to peak short, middle and long wavelengths is limited only to some primate species. In Old and New World primates a second photopigment has appeared repeatedly during phylogeny, allowing red colors to be distinguished from yellows and greens. Several hypotheses aspire to explain the adaptive benefits of trichromatic vision for primates. The predominant one is foraging adaptation for facilitation visual detection of fruits or young leaves. Alternative explanations are based on the function of red color in aposematic signaling or its role in socio-sexual communication. We tested spontaneous color preference in macaque monkeys (Macaca mulatta) for both food and non-food objects in a laboratory environment. We hypothesized that preference for or avoidance of red color together with the context of such behavior may help us to understand what the adaptive advantage leading to a rapid expansion of a gene for a second pigment in the long-wavelength region was. We found neither preference nor avoidance toward red color in non-food objects, but we found a significant preference for red color in food; therefore, we suggest that the results support the foraging hypothesis in macaque monkeys.
Keywords: Animals; Color Vision; výběrové chování; ovoce; vidění barevné; zvířata; mužské pohlaví; Macaca mulatta; Male; Choice Behavior; Fruit